A DNA Polymorphism Discovery Resource for Research on Human Genetic Variation: Table 1. - Francis S. Collins; Lisa Brooks; Aravinda Chakravarti (1998)
perform association analysis on many affected and unaffected individuals, which would require hundreds of thousands of variants spread over the entire genome (Risch and Merikangas 1996). Such a large number of variants is currently not available. The DNA Polymorphism Discovery Resource is designed to promote their discovery. About 90% of sequence variants in humans are differences in single bases of DNA, called single nucleotide polymorphisms (SNPs). SNPs in the coding regions of genes (cSNPs) or in regulatory regions are more likely to cause functional differences than SNPs elsewhere. Although most SNPs do not affect gene function, a large number of mapped SNPs will be valuable as markers throughout the genome for finding SNPs that do affect gene function, as linkage disequilibrium over tens to hundreds of kilobases is expected to be found in many regions of the human genome. Both SNPs and cSNPs can be identified by using the DNA Polymorphism Discovery Resource. When two random chromosomes are